Prácticas de cuidado entre mujeres en contextos de desplazamiento forzado interno - Montalvo González, Alethia (El Colegio de México, 2025)
The objective of this research is to ethnographically explore the care practices implemented by women in contexts of internal forced displacement. Through ethnographic landscapes structured around case studies —developed via in-depth interviews and participant observation in the field— this study highlights the direct and indirect care practices these women deploy to sustain the lives of their companions. I argue that experiences of internal forced displacement are diverse and composed of multiple trajectories, in which care practices are fundamental to understanding the decisions women make when choosing specific destinations, displacement routes, and strategies to ensure the safety of those who accompany them.